Distribution Analysis And Environmental Impact Of Heavy Metal Contamination In Rice Fields: A Case Of Sleman Regency, Yogyakarta, Indonesia (Journal of Namibian Studies : History Politics Culture, 2023)
Examining the heavy metals' contamination in soil is important yet haven’t much done in Sleman, Yogyakarta, Indonesia. The research aims to determine the distribution and pollution levels of Pb, Cu, As, Cr, Ni in Sleman's paddy fields. The composite soil samples were collected from 23 irrigated lowland fields of 15 subdistricts in Sleman using the grid sampling method. The analysis of heavy metal contamination including contamination factor (CF), pollution load index(CLI), ecological risk assessment (Er),potential ecologica risk index (RI),enrichment factor(EF), and geoaccumulation index (Igeo). The results detected the soil contamination of Cu, Pb, As, Cr and Ni from all sampling points. There was high-level contamination factor of Cu (CF =7.69), medium-level contamination factor of Pb (CF = 2.23) and As (CF = 1.67), and low-level contamination factor of Cr and Ni (CF < 1). Cr and Ni were derived from natural processes, but Cu, Pb, and As contaminants were anthropogenically produced. Cu, Pb, As, Cr, and Ni metals have a low potential ecological risk (Er